Family Support System and Psychological Well Being in Patients with Chronic Kidney Disease - Anggraini, Merry Tiyas; Alif Antoni, Asyam Baihaqi; Faizin, Chamim; Lahdji, Aisyah (Journal of Educational, Health and Community Psychology, 2024)
Patients with chronic kidney disease rely on hemodialysis therapy for life support, and this treatment can impact their psychological well-being. Family support is a crucial factor influencing psychological well-being in these patients. This study aims to investigate the correlation between family support and the psychological well-being of chronic kidney disease patients. The research employed an observational analytic cross-sectional design, with respondents being patients at Roemani Hospital in Semarang who underwent hemodialysis in October 2022. The study utilized questions to assess perceived social support from family and a psychological well-being scale. The statistical analysis employed the Spearman rank test, revealing a strong relationship between family support and the psychological well-being of chronic kidney disease patients, with a positive correlation (p = 0.001, r = 0.661). The findings suggest that higher levels of family support are associated with better psychological well-being in chronic kidney disease patients undergoing hemodialysis.